2021
DOI: 10.1007/s12517-021-07854-1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of rock size on the mechanical behavior and deformation performance of soil-rock mixture: a meso-scale numerical and theoretical study

Abstract: Rock size has a significant impact on the mechanical behavior and deformation performance of soil-rock mixture. This paper aims at investigating and isolating the effect of rock size on the soil-rock mixture in mechanical behavior and deformation behavior and making clear how this factor influences them. Taking the material heterogeneity into account, a two-dimensional meso-scale numerical method for modeling soil-rock mixture is presented, which considers the rocks and soil matrix as separate constituents. Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 25 publications
(24 reference statements)
0
2
0
Order By: Relevance
“…Ren et al (Ren et al, 2021) established an equivalent model for fractured rock masses and obtained the relationship between E and seepage parameters. Zhang et al (Zhang and Li, 2021) investigated the macroscopic mechanical behavior of 160 sets of soil rock mixtures with different sizes and discovered the variation of deformation modulus with rock size.…”
Section: Introductionmentioning
confidence: 99%
“…Ren et al (Ren et al, 2021) established an equivalent model for fractured rock masses and obtained the relationship between E and seepage parameters. Zhang et al (Zhang and Li, 2021) investigated the macroscopic mechanical behavior of 160 sets of soil rock mixtures with different sizes and discovered the variation of deformation modulus with rock size.…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have studied the mechanical properties and failure mechanism of the SRM from different points of view by using experimental and numerical methods, including meso-structural characteristics (block size, position, content, shape etc.) [3,[5][6][7], strength parameters [8][9][10][11], and shear strength [9,12,13]. Despite the fact that these research efforts used to obtain the macromechanical responses of the SRM, it is difficult to thoroughly reveal the meso-scale mechanical properties of the SRM.…”
Section: Introductionmentioning
confidence: 99%
“…However, the contrary conclusion has also been proposed, and the decrease in strength of S-RM can be found as the particle size increases. Zhang and Li (2021) compared the mechanical behaviors of S-RM samples with various rock sizes using the mesoscale numerical method and found that the sample with the smaller rock size presented a greater peak strength. The negative correlation between strength and particle size has also been suggested by Kang (2016) and Hamidi et al (2012).…”
Section: Introductionmentioning
confidence: 99%